Geographical indication certification of agricultural products and agricultural carbon emissions—empirical evidence from China - Zhang, Yu; Liu, Yanping (Frontiers in Sustainable Food Systems, 2025)
Geographical Indications for Agricultural Products (GIAP), as an intellectual property protection system, hold potential for driving agricultural green transformation. However, their impact mechanisms on agricultural carbon emissions (ACE) remain unclear. This study empirically investigates their impact using provincial panel data from China spanning 2004 to 2022 and employs a difference-in-differences (DID) model. The results indicate that the implementation of GIAP systems has a significant positive effect on reducing agricultural carbon emissions, each additional GIAP certification reduces ACE intensity by 0.3679 units on average. The conclusion that remains robust across a variety of specification tests. Mechanism analysis demonstrates that GIAP effectively lower agricultural carbon emissions primarily by facilitating farmland transfer, strengthening agricultural socialized services, increasing the proportion of grain crops, and improving technical efficiency. Furthermore, the empirical findings reveal significant spatial spillover effects associated with GIAP. Additional heterogeneity analysis shows that the carbon emission reduction effects of GIAP vary substantially across different regions, economic zones, functional areas, and “hot” and “cold” spatial clusters. Based on these findings, it is recommended that greater emphasis be placed on the development and refinement of the GIAP system, and that regionally differentiated strategies be adopted to further integrate GIAP policy with agricultural carbon reduction initiatives, thereby laying a solid institutional foundation for the green and low-carbon transformation of agriculture.